2012
DOI: 10.1002/dvdy.23759
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 is required in endothelial but not myocardial cell lineages during cardiovascular development

Abstract: Background: The forkhead transcription factor FoxO1 is involved in cell cycle regulation during cardiovascular development. Systemic loss of FoxO1 results in lethality at embryonic day 10.5 with severe cardiovascular defects; however, the cell-type-specific requirements for FoxO1 in cardiovascular development are unknown. Here we examine the role of FoxO1 using a conditional loss of function approach. Results: Loss of FoxO1 in differentiated cardiac myocytes has no apparent effect on cardiovascular development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
2
21
1
Order By: Relevance
“…However, another study reported that endothelial-specific deletion of FoxO1 is embryonic lethal 16 . Conditional deletion of all three FoxO factors in the endothelium is compatible with survival and protects against atherosclerosis in low-density lipoprotein receptor knockout mice 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, another study reported that endothelial-specific deletion of FoxO1 is embryonic lethal 16 . Conditional deletion of all three FoxO factors in the endothelium is compatible with survival and protects against atherosclerosis in low-density lipoprotein receptor knockout mice 17 .…”
Section: Introductionmentioning
confidence: 99%
“…37 Endothelial-specific FoxO1 knockout showed defective vasculature remodeling and lethality at E10.5, suggesting that endothelial FoxO1 is essential to cardiovascular development. 41 Interestingly, FoxO3, another member of the FoxO family, was reported to regulate neuronal differentiation. In adult neural precursor cells, ASCL1, a proneuronal bHLH transcription factor, shares common targets with FoxO3 and FoxO3 could inhibit ASCL1-dependent transcription of neurogenic genes.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, Foxo1 activation following IRS2 deficiency, in the brain enhanced longevity, but promoted obesity and diabetes (Taguchi, et al 2007). Also, Foxo1 activation enhances myocardial survival upon induction of oxidative stress (Sengupta, et al 2012; Sengupta, et al 2011; Sengupta, et al 2009), and autophagy, for control of cell size following serum starvation (Sengupta et al 2009). Mice lacking systemic Foxo1 are embryonic lethal, since Foxo1 is required for endothelial cell lineage during cardiovascular development (Hosaka et al 2004; Sengupta et al 2012).…”
Section: Part 2: Mechanisms For Insulin Resistancementioning
confidence: 99%
“…Also, Foxo1 activation enhances myocardial survival upon induction of oxidative stress (Sengupta, et al 2012; Sengupta, et al 2011; Sengupta, et al 2009), and autophagy, for control of cell size following serum starvation (Sengupta et al 2009). Mice lacking systemic Foxo1 are embryonic lethal, since Foxo1 is required for endothelial cell lineage during cardiovascular development (Hosaka et al 2004; Sengupta et al 2012). In C. elegans , the Foxo1 ortholog Daf-16 enhances longevity when insulin/IGF-1 receptor signaling is inactivated, and potentially increases expression of anti-oxidative genes (MnSOD), and also stimulates lipid droplet accumulation (Ogg, et al 1997).…”
Section: Part 2: Mechanisms For Insulin Resistancementioning
confidence: 99%